2020
DOI: 10.1177/1049732320956267
|View full text |Cite
|
Sign up to set email alerts
|

“The Food Matches the Mood”: Experiences of Eating Disorders in Bipolar Disorder

Abstract: Approximately 33% of those with bipolar disorder (BD) have a comorbid eating disorder (ED). However, the trajectory of these conditions has received little research attention. Nine participants who met criteria for BD and an ED participated in qualitative interviews exploring experiences of illness onset, the interaction of these conditions, and service provision. Almost all participants in the sample reported minimal to no screening of ED problems, despite their health professionals’ frequent discussion of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Comparatively, descriptive studies in the literature reported that smoking affected emotional eating behavior and BMI values in adults and adolescents (Jones et al, 2019). In one qualitative study that was conducted to investigate the experiences of bipolar patients with eating disorders, patients stated that eating problems increased during depressive periods, that drug treatment triggered their eating problems, and that eating problems in particular caused weight gain (McAulay et al, 2021). In another qualitative study conducted to investigate the eating behaviors of patients with schizophrenia, it was stated that making changes to the amount of food, food‐intake hours, and food‐related delusions might cause eating problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, descriptive studies in the literature reported that smoking affected emotional eating behavior and BMI values in adults and adolescents (Jones et al, 2019). In one qualitative study that was conducted to investigate the experiences of bipolar patients with eating disorders, patients stated that eating problems increased during depressive periods, that drug treatment triggered their eating problems, and that eating problems in particular caused weight gain (McAulay et al, 2021). In another qualitative study conducted to investigate the eating behaviors of patients with schizophrenia, it was stated that making changes to the amount of food, food‐intake hours, and food‐related delusions might cause eating problems.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in appetite resulting from the use of antipsychotic drugs in individuals can cause confusion in basic eating behaviors, such as monitoring hunger and satiety signals and understanding the nutritional needs of the body affecting nutrition (Aguiar-Bloemer et al, 2018). In addition, an increase in cortisol levels, which occurs as a result of the inability of individuals to use effective methods to cope with stress related to disease symptoms, may cause individuals to prefer easier and faster nutrition (McAulay et al, 2021). Among those individuals with chronic mental disorders, anxiety over body image that had deteriorated due to obesity has been found to increase eating-related stress (Kouidrat et al, 2018).…”
mentioning
confidence: 99%
“…However, little is known about the timing of symptom onset, the individual trajectories of the disorders when co-occurring and the interaction of symptoms (Thiebaut et al 2019 ). Data from a qualitative study suggest that in some patients symptoms of the eating disorder preceded the onset of BD (McAulay et al 2021 ). Clinicians have to evaluate and monitor patients with BD and at-risk for BD for the presence and the development of any comorbid psychiatric condition to ensure appropriate interventions while avoiding potential iatrogenic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Food nutrition is an important part of a daily diet and can have a profound effect on emotions, personalities, cognitive functioning, and moods. Bipolar disorder affects 5.7 million people or 2.6% of all people [41,24]. Many people diagnosed with bipolar disorder have rapid mood swings among other clinical symptomology.…”
Section: Nutrition and Bipolar Disordermentioning
confidence: 99%
“…There is a 40 to 70% chance that individuals with bipolar disorder also have an alcohol use issue, [6,21,22] which complicates treatment approaches as well as creates risk factors with the usage of antipsychotic medications [7]. Those with bipolar disorder, post-traumatic stress disorder, and anxiety disorders are more likely to engage in unhealthy habits like tobacco usage, eating disorders, and binge drinking [7,23,24,25]. For optimal management ofbipolar disorder and PTSD, avoiding alcohol is highly recommended, and the consumption of a healthy diet with nutrient-dense foods may contribute to improved mental and physical health.…”
Section: Introductionmentioning
confidence: 99%